Rapidly evolving gangrenous vasculitis in a critically ill patient with ulcerative colitis: a case report. (2nd May 2023) - Rotimi, Oloruntobi; Sollei, Tamas; Dheansa, Baljit; Thomson, David; White, Nicola; Grimes, Caris E
Abstract : Ulcerative colitis is a disease characterised by non-granulomatous submucosal inflammation ranging from isolated proctitis to colitis. Extra-intestinal manifestations of the condition occur in multiple organ systems, with dermatological complications occurring commonly. This case report aims to highlight an uncommon dermatological complication of ulcerative colitis with particular focus on patient care and management.